2007
DOI: 10.1136/adc.2006.112862
|View full text |Cite
|
Sign up to set email alerts
|

Increasing prevalence of hypospadias in Western Australia, 1980-2000

Abstract: Hypospadias affects one in 231 births and has been reported to have increased significantly over the last 20 years. Future investigation of the aetiology of hypospadias is important to identify potentially modifiable risk factors and ensure optimal male reproductive health in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
63
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(70 citation statements)
references
References 25 publications
(12 reference statements)
5
63
0
1
Order By: Relevance
“…The present study found that isolated hypospadias is the main type of hypospadias occurring in China, accounting for 84.55% of overall cases, which is similar to the report from Australia (Nassar et al, 2007). The prevalences of overall and isolated hypospadias in China were 9.03 and 7.64 per 10,000 male births, respectively, and lower than in the data reported by other countries or regions.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The present study found that isolated hypospadias is the main type of hypospadias occurring in China, accounting for 84.55% of overall cases, which is similar to the report from Australia (Nassar et al, 2007). The prevalences of overall and isolated hypospadias in China were 9.03 and 7.64 per 10,000 male births, respectively, and lower than in the data reported by other countries or regions.…”
Section: Discussionsupporting
confidence: 81%
“…Currently, the time trends of hypospadias prevalence in other countries worldwide are not consistent. Australia (Nassar et al, 2007), Denmark (Lund et al, 2009), and the United Kingdom (Abdullah et al, 2007a) have reported increasing trends in hypospadias prevalence, whereas Japan (Kurahashi et al, 2004), Scotland (Ahmed et al, 2004), and the U.S. states of New York (Fisch et al, 2009), Washington (Porter et al, 2005), and California (Carmichael et al, 2003) have reported no significant increases. In addition, regional differences in hypospadias prevalences have been reported; for example, a spatial clustering of hypospadias prevalences was found in northern England (Abdullah et al, 2007a).…”
Section: Introductionmentioning
confidence: 93%
“…Hypospadias is one of the most common congenital malformations in males, affecting 1 in 250-300 individuals at birth (Nassar et al, 1997;Ghirri, et al, 2009). The occurrence of hypospadias has been linked to genetic, endocrine, and several environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…In the last 30 years there is an increase in the prevalence of hypospadias. [10][11][12][13][14] The aim of hypospadias surgery is to obtain a functional and cosmetically normal penis. More than 300 different techniques have been explained in the treatment of hypospadias.…”
Section: Discussionmentioning
confidence: 99%